Microorganismos nativos en la eficiencia de remoción de materia orgánica del efluente de la estación depuradora de Calceta, Manabí - Bazurto Meza, Leonardo Sebastián (2017)
The objective of this study was to evaluate the efficiency of a microbial consortia consisting of (Bacillus sp., Aspergillus oryzae) to achieve removal organic matter in domestic wastewater from Calceta sewage treatment plant. The research encompassed two phases: in the first phase, it was collected water samples and a microbiological follow up was done of moulds, yeasts and bacteria to obtain cultures of microorganisms and to and classify them by macroscopical and microscopical morphological characterization, to form a microbial consortia. In the second phase, it was determined the microorganisms suitable for primary treatment of domestic wastewater by a systematic review of the literature. We then inoculated the experimental units containing 2 dm3 of wastewater with an initial biochemical oxygen demand of 480 mg/dm3. A single completely randomized design was used with 4 treatments and 3 replicates: for this we evaluated parameters such as demand biochemistry of oxygen, hydrogen potential and dissolved oxygen, resulting in a treatment with a dose of 5 cm3/dm3 recorded a final biochemical oxygen demand of 37 mg/dm3 had a 92% removal efficiency. Treatment with doses of 10 cm3/dm3 with a final biochemical oxygen demand of 57 mg/dm3 presented a removal efficiency of 88% and treatment three with doses of 15 cm3/dm3 with a final biochemical oxygen demand of 67 mg/dm3 and a removal efficiency of 86 %. It is concluded that the microorganisms Bacillus sp and Aspergillus oryzae in doses of 5cm3 allowed a high removal of organic matter (92%) with the application of the native microbial consortium.